Identification and characterization of Burkholderia pseudomallei K96243 serine and metallopeptidases - Muhamad Bunnori, Noraslinda; Mohamed, Rahmah (Elsevier Ltd., 2012)
products, including proteases. The role of these proteases in the melioidosis, however, remains obscure. Previous findings have hinted at the inherent pathogenicity of the protease during B. pseudomallei K96243 infection. We chose to study the two major families peptidases, i.e. serine peptidases and metallopeptidases present in B. pseudomallei K96243. The data mining revealed eighty ORFs (open reading frame) that potentially code for these peptidases and have prominent homology with B. pseudomallei K96243 based on prediction of function by bioinformatics approach. The annotations and classification lead forty eight and thirty two putative peptidases belong to serine peptidase and metallopeptidase,respectively. The distribution of 98% from the identified putative peptidase belongs to endopeptidases (EC 3.4.21. and EC 3.4.24.) and exopeptidases (EC 3.4.11., EC 3.4.13., EC 3.4.14., EC 3.4.16. and EC 3.4.17) and another 2% belong to EC 3.5.